Designing and Simulation for Vertical Moving Control of UAV System using PID, LQR and Fuzzy logic - Mohamad Reza Rahimi; Saeide Hajighasemi; Davoud Sanaei (International Journal of Electrical and Computer Engineering (IJECE), 2013)
This paper presents the designing and simulation for vertical moving controlof Unmanned Air Vehicles (UAV) system using Proportional IntegralDerivative (PID) control method, Linear Quadratic Regulator (LQR) controlmethod and fuzzy logic control technique.The UAV system pose a challengercontrol problem that in it precise model of system is non-linear. Theconventional PID controller, the LQR controller, Fuzzy Logic Controller(FLC) and Self-Tuning Fuzzy PID controller are designned based on thedynamic modeling of the system is derived from a suitable mathematicalmodel to describe the vertical motion of a UAV. Simulation results in Matlaband Simulink show that by using self-tuning Fuzzy PID, the performance ofvertical moving control system is improved significantly compared to Othercontrollers.DOI:http://dx.doi.org/10.11591/ijece.v3i5.3440